Flow Analysis of Intake Manifold Using Computational Fluid Dynamics - Saiful Azam, Syafiqah Ruqaiyah; Zainal Abidin, Shaiful Fadzil; Ishak, Izuan Amin; Khalid, Amir; Mustaffa, Norrizal; Taib, Ishkrizat; Sukiman, Safra Liyana; Darlis, Nofrizalidris (International Journal of Integrated Engineering, 2023)
The main element of the air intake system is an intake manifold. These are the main components which control the flow value that will be used in the combustion chamber. The aim of this study is to analyse the velocity of flow distribution in all runners and to compare the design of intake manifold in previous study. Simulations are performed on two types of intake manifold design which are Design 1, the inlet end is located next to the regulator chamber whilst for Design 2, the inlet end is located in the middle of regulator chamber. Intake manifold parameters such as velocity distribution, unevenness and pressure losses along the runner are used to determine the better design for better performance. From the results, the velocity and the pressure of intake manifold of these two types of design are determined. Compared with previous study, the velocity difference is 0.05%. This showed that the simulation result obtained in this study is in accordance with previous study. Next, the percentage difference between Design 1 and previous design is approximately 4%. Furthermore, the pressure losses between Design 1 and Design 2 are 0.3% and Design 1 achieved the range of acceptable values between 2500Pa to 3000Pa. The results of the velocity distribution, the evenness of each runner and the value of pressure losses shows that Design 1 met all the criteria and exhibited the best design improvement as compared to the previous design with 2% improvement.